Coevolution of Two Sulfonylurea-Resistant Common Chickweed (Stellaria media) Biotypes with Different Mutations in the Acetolactate Synthase Gene. Issue 4 (2nd July 2018) - Laforest, Martin; Soufiane, Brahim
Abstract: Common chickweed [ Stellaria media (L.) Vill.] is an annual weed found in grain fields and pastures. This creeping weed produces a mat-like canopy that competes with crop seedlings for light and nutrients. This species is almost exclusively autogamous. Acetolactate synthase (ALS)-inhibiting herbicides are frequently used to control this broadleaf weed, and two mutations in the S. media ALS gene (Pro-197-Gln and Trp-574-Leu) have been reported to confer herbicide resistance. Seeds from several plants that survived an application of thifensulfuron-methyl/tribenuron-methyl (16 g ai ha −1 ) were collected from the same field in Québec, Canada. Seedlings were grown, tested for the presence of mutations in the ALS gene, and treated with different rates of foramsulfuron, flumetsulam, and imazethapyr, each belonging to different families of ALS inhibitors. Two herbicide resistance–conferring mutations were identified in this population. One biotype had the previously reported Pro-197-Gln, while a new mutation, Pro-197-Ser, was identified in different plants from the same population. The new mutation (Pro-197-Ser) confers a lower level of resistance to sulfonylureas than Pro-197-Gln, and both biotypes are susceptible to imizadolinone and triazolopyrimidines.